Checklists of Parasites of Farm Fishes of Babylon Province, Iraq - Furhan T. Mhaisen; Abdul-Razzak L. Al-Rubaie (Journal of Parasitology Research)
Literature reviews of all references concerning the parasitic fauna of fishes in fish farms of Babylon province, middle of Iraq, showed that a total of 92 valid parasite species are so far known from the common carp (Cyprinus carpio), the grass carp (Ctenopharyngodon idella), and the silver carp (Hypophthalmichthys molitrix) as well as from three freshwater fish species (Carassius auratus, Liza abu, and Heteropneustes fossilis) which were found in some fish farms of the same province. The parasitic fauna included one mastigophoran, three apicomplexans, 13 ciliophorans, five myxozoans, five trematodes, 45 monogeneans, five cestodes, three nematodes, two acanthocephalans, nine arthropods, and one mollusc. The common carp was found to harbour 81 species of parasites, the grass carp 30 species, the silver carp 28 species, L. abu 13 species, C. auratus one species, and H. fossilis one species. A host-parasite list for each fish species was also provided.